Genetic relatedness, virulence, and drug susceptibility of Campylobacter isolated from water and wild birds - Andrzejewska, Małgorzata; Grudlewska-Buda, Katarzyna; Śpica, Dorota; Skowron, Krzysztof; Ćwiklińska-Jurkowska, Małgorzata; Szady-Grad, Małgorzata; Indykiewicz, Piotr; Wiktorczyk-Kapischke, Natalia; Klawe, Jacek J. (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction This study aimed to identify the characteristics of Campylobacter isolated from wild birds (Black-headed gulls Chroicocephalus ridibundus and Great tits Parus major) and collect surface water samples (from rivers, ponds, ornamental lakes, freshwater beaches). Research material included 33 Campylobacter isolates. All the strains were isolated by different monitoring and surveillance plans. Methods The prevalence of selected genes (flaA, cadF, iam, cdtB, wlaN, sodB, tet0) encoding virulence factors and resistance among Campylobacter spp. was assessed by the PCR method. The genetic similarities of isolates were determined by Pulsed-Field Gel Electrophoresis (PFGE). The susceptibility of Campylobacter isolates to clinically important antimicrobials: erythromycin, tetracycline, and ciprofloxacin, previously assessed by E-test, was presented in the form of drug susceptibility profiles depending on the origin of the isolates. Results The cadF, flaA, cdtB, and sodB genes exhibited the highest detection rate. Statistically significant differences between the presence of wlaN virulence genes were noted among different species of the isolates. No genetically identical isolates were found. The most numerous antibiotic susceptibility profile included strains susceptible to all antibiotics studied (profile A-33.3%). The second most common were the tetracycline - and ciprofloxacin-resistant (profile B-27.2%), and tetracycline-resistant profile (C-24.2%) respectively. Discussion The study revealed the virulent properties of Campylobacter isolated from water samples, and wild birds, and high resistance rates to tetracycline, and fluoroquinolones. The lack of genetic relatedness among strains isolated from water, and birds may indicate other sources of surface water contamination with Campylobacter bacteria than birds. The presence of Campylobacter spp. in wild birds could also have other environmental origins.